El baile para mejorar el desarrollo motriz grueso en niños de inicial ii de la unidad educativa del milenio Bernardo Valdivieso de la ciudad de Loja, período 2019 – 2020. - Rivera Jiménez, Jean Carlos (2021)
In this thesis entitled: THE DANCE TO IMPROVE GROSS MOTOR DEVELOPMENT IN CHILDREN OF INITIAL II OF MILLENNIUM EDUCATIONAL UNIT “BERNARDO VALDIVIESO” OF LOJA CITY, PERIOD 2019 - 2020, the general objective was formulated: To demonstrate that dance helps the gross motor development in children of Initial II. The inductive, deductive, analytical-synthetic, descriptive and comparative methods helped in the realization of the present scientific investigation; The instruments applied were: the survey, directed at 3 pre-school teachers, and the Cruz y Mazaira Psychomotor Assessment Scale, which was applied to 21 children between 4 and 5 years of age. In the pre-test results, a low level of motor skills was evidenced, 95% in locomotion and 100% in balance, leg coordination and in the recognition of the body scheme in another. In order to contribute to the solution of the problem, an activity guide called: Different types of dance was created and applied to improve the development of gross motor skills in children aged 4 to 5 years, where a considerable increase in the motor skills to good, 85% in locomotion, 95% in balance, 62% in coordination of the legs and 90% in the recognition of the body scheme in others. Concluding that the dance worked constantly improves the gross motor skills of children from 4 to 5 years old and it is important to continue stimulating their motor skills to discover and enhance the skills and abilities they have.